Islamic Civilization in Thirty Lives : The First 1000Years - Robinson, Chase F. (London Thames & Hudson, 2018)
Religious thinkers, political leaders, lawmakers, writers, and philosophers have shaped the 1,400-year-long development of the world's second-largest religion. But who were these people? What do we know of their lives and the ways in which they influenced their societies? In Islamic Civilization in Thirty Lives, the distinguished historian of Islam, Chase F. Robinson draws on the long tradition in Muslim scholarship of commemorating in writing the biographies of notable figures, but he weaves these ambitious lives together to create a rich narrative of Islamic civilization, from the Prophet Muhammad in the seventh century to the era of the world conquerer Timur and the Ottoman Sultan Mehmed II in the fifteenth. Beginning in Islam's heartland, Mecca, and ranging from North Africa and Iberia in the west to Central and East Asia, Robinson not only traces the rise and fall of Islamic states through the biographies of political and military leaders who worked to secure peace or expand their power, but also discusses those who developed Islamic law, scientific thought, and literature. What emerges is a fascinating portrait of rich and diverse Islamic societies.
Include Color Illustrations, Glossary, Notes, Bibliography and Index
Keywords: Middle East -- Islamic civilization -- Intellectual life -- Civilization, Arab